First-pass Metabolism of Decursin, a Bioactive Compound of Angelica gigas, in Rats - Park, Hyun Seo; Kim, Byunghyun; Oh, Ju-Hee; Kim, Young Choong; Lee, Young-Joo (Planta Medica, 2012)
Decursin is considered the major bioactive compound of Angelica gigas roots, a popular Oriental herb and dietary supplement. In this study, the pharmacokinetics of decursin and its active metabolite, decursinol, were evaluated after the administration of decursin in rats. The plasma concentration of decursin decreased rapidly, with an initial half-life of 0.05 h. It was not detectable at 1 h after intravenous administration at an area under the plasma concentration-time curve of 1.20 µg · mL−1·h, whereas the concentration of decursinol increased rapidly reaching a maximum concentration of 2.48 µg · mL−1 at the time to maximum plasma concentration of 0.25 h and an area under the plasma concentration-time curve of 5.23 µg · mL−1·h. Interestingly, after oral administration of decursin, only decursinol was present in plasma, suggesting an extensive hepatic first-pass metabolism of decursin. The extremely low bioavailability of decursin after its administration via the hepatic portal vein (the fraction of dose escaping first-pass elimination in the liver, FH = 0.11) is indicative of extensive hepatic first-pass metabolism of decursin, which was confirmed by a tissue distribution study. These findings suggest that decursin is not directly associated with the bioactivity of A. gigas and that it may work as a type of natural prodrug of decursinol.
Keywords: decursin; decursinol; first-pass metabolism; absorption barrier; Angelica gigas Nakai; Apiaceae